(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Physical inactivity rates in Scotland remain persistently high in young people. According to the 2022 Scottish Health Survey, 13-to-15-year-olds were the least likely to meet physical activity recommendations in Scotland, with only 54% achieving the recommendations. Addressing this has been an enduring societal challenge over the last 25 years. Project Description: Paths for All – Scotland’s walking charity – in partnership with the Universities of Stirling, Edinburgh, and the Highlands and Islands, are extending the demographic reach of their work by using co-production to develop a new walking challenge intervention to support young people’s physical, mental, and social health. This project is using the latest thinking in behaviour change theory and understanding of how digital technology (such as mobile phones, smart watches, and apps) can support the promotion of physical activity in young people, to develop bespoke offers for young people in high school settings. Another outcome of this project is to empower young people to increase their awareness of physical activity and digital health data literacy. The co-production work is taking place between March and December 2025: A series of workshops are being run with five to eight adolescents representing six high schools from across Scotland. The outputs and learning from the workshops with young people will shape and inform the final product and this could include the development of digital tools, messaging, and communications, the look/feel of the resource and communications that support the intervention design. The presentation will detail the practicalities of how to successfully design and deliver co-production activities and lessons learned and will consider how the design of the workshops ensures that young people have a significant and meaningful say in shaping the output of this project. Conclusion: This project contributes to a growing body of work addressing physical inactivity in young people in high school settings. Using co-production methods, a goal of the project is producing an exemplar of physical activity intervention design by young people, for young people in high school settings.